Map Drawing Method Based on Visual - Luo, Zongheng; Lu, Jun (International Journal of Computer Science and Information Technology, 2024)
In order to achieve map drawing for robots under resource limited conditions, this paper proposes a map drawing method based on image processing technology. By using visual processing techniques, map drawing work can be achieved. After experiments, the effectiveness of this method has been proven, and the error caused in an environment of 100cm * 60cm does not exceed 40mm.